Natural history and biomarkers in hereditary sensory neuropathy type 1. Issue 4 (11th February 2015) - Fridman, Vera; Oaklander, Anne louise; David, William S.; Johnson, Elise A.; Pan, Jessica; Novak, Peter; Brown, Robert H.; Eichler, Florian S.
ABSTRACT: Introduction : Hereditary sensory and autonomic neuropathy type 1 (HSAN1) is most commonly caused by missense mutations in SPTLC1 . In this study we mapped symptom progression and compared the utility of outcomes. Methods : We administered retrospective surveys of symptoms and analyzed results of nerve conduction, autonomic function testing (AFT), and PGP9.5‐immunolabeled skin biopsies. Results : The first symptoms were universally sensory and occurred at a median age of 20 years (range 14–54 years). The onset of weakness, ulcers, pain, and balance problems followed sequentially. Skin biopsies revealed universally absent epidermal innervation at the distal leg with relative preservation in the thigh. Neurite density was highly correlated with total Charcot‐Marie‐Tooth Examination Score (CMTES; r 2  = −0.8) and median motor amplitude ( r 2  = −0.75). Conclusions : These results confirm sensory loss as the initial symptom of HSAN1 and suggest that skin biopsy may be the most promising biomarker for future clinical trials. Muscle Nerve, 2015 Muscle Nerve 51: 489–495, 2015